Ly9 (CD229) Antibody Targeting Depletes Marginal Zone and Germinal Center B Cells in Lymphoid Tissues and Reduces Salivary Gland Inflammation in a Mouse Model of Sjögren's Syndrome - Puñet-Ortiz, Joan; Sáez Moya, Manuel; Cuenca, Marta; Caleiras, Eduardo; Lazaro, Adriana; Engel, Pablo (Frontiers in Immunology, 2018)
Sjögren’s Syndrome (SjS) is a common chronic autoimmune disease characterized by the B cell hyperactivation, lymphocyte infiltration and tissue damage of exocrine glands. It can also present life-threating extraglandular manifestations, such as pulmonary and hepatic involvement, renal inflammation and marginal zone (MZ) B cell lymphoma. Several biologic agents have been tested in SjS but none has shown significant efficacy. Here, we report the effects of Ly9 (CD229) antibody targeting, a cell surface molecule that belong to the SLAM family of immunomodulatory receptors, using NOD.H-2h4 mice as a model of SjS-like disease. Female mice were treated with anti-Ly9 antibody or isotype control at week 24, when all mice present SjS related autoantibodies, salivary gland infiltrates and marginal zone (MZ) B cell pool enlargement. Antibody injection depleted key lymphocyte subsets involved in SjS pathology such as MZ, B1 and germinal center B cells in spleen and draining lymph nodes without inducing a general immunosuppression. Importantly, mice receiving anti-Ly9 mAb showed a reduced lymphocyte infiltrate within salivary glands. This reduction may be, in part, explained by the down-regulation of L-selectin and alfa4/beta7 integrin induced by the anti-Ly9 antibody. Furthermore, levels of anti-nuclear autoantibodies were reduced after anti-Ly9 treatment. These data indicate that Ly9 is a potential therapeutic target for the treatment of SjS.